Reorienting Economic Justice: A Critical Analysis of Economic Exegesis (Tafsir Ayat Ekonomi) in Contemporary Sharia Finance - Renatha Aprilia; Achmad Basofitrah; Indah Maslaha; Imatun Sa’adia; Maysara (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study examines the role of the interpretation (tafsir) of economic verses in the Qur’an in constructing a just economic system, with a focus on the Indonesian context. The research is motivated by persistent issues of economic inequality and the limited integration of ethical-religious values into contemporary economic practices. A qualitative approach using library research was employed to analyze and synthesize classical and contemporary tafsir literature, as well as scholarly works in Islamic economics. The study applies a descriptive-analytical and content analysis method to explore how economic principles derived from Qur’anic interpretation can contribute to the development of equitable economic frameworks. The findings reveal that tafsir of economic verses consistently emphasizes key principles such as distributive justice, prohibition of riba, social responsibility, and collective welfare. However, the application of these principles varies significantly depending on interpretative approaches, methodological orientations, and socio-cultural contexts. The study also identifies a shift in contemporary scholarship from purely textual interpretations toward more contextual and interdisciplinary approaches, aiming to address modern economic challenges. Despite this progress, a significant gap remains in integrating normative tafsir with practical economic implementation. This research contributes to the literature by offering a critical and integrative analysis that bridges classical Islamic scholarship and contemporary economic discourse. It highlights the importance of contextualizing tafsir to ensure its relevance in addressing real-world economic issues. The study provides both theoretical and practical implications, suggesting that tafsir should be positioned as a dynamic framework capable of guiding ethical and sustainable economic development. Nevertheless, this study is limited by its reliance on secondary data and lack of empirical validation. Future research is recommended to incorporate empirical methods and interdisciplinary approaches to test the applicability of tafsir-based economic models. Overall, this study affirms that the interpretation of economic verses holds significant potential in shaping a just and inclusive economic system when applied critically and contextually.